PENETAPAN KONTRAK HARGA UNTUK PENINGKATAN KERJA SAMA ANTARA PETERNAK DAN PEDAGANG (PENGEPUL) JANGKRIK DI KECAMATAN KEBONAGUNG KABUPATEN DEMAK - Astohar, Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2013)
Cricket animals are animals that have high economic value,which is used for animal feed (birds and ornamental fish). This makessome people or community groups cultivate these crickets. The object ofthis research is the cricket farmers in Kecamatan Kebonagung DemakRegency. This breeder is divided into two groups, the farmers whocooperate with the collectors and who do not cooperate. For farmers whodo not cooperate with financial collectors and information better thanthose who work together. The focus of this study is whether thedetermination of price contracts can enhance cooperation betweenfarmers and traders (Collectors) Crickets in Kebonagung District,Demak District.The population in this research is all breeders andcollectors (traders) crickets in Kebonagung District, Demak Districtwhich is still actively running the farm and business of crickets is asmuch as 53 breeders and collectors. The sample is taken by 7 informants,2 cricket farmers, 2 collectors collectors, 1 feeder, 1 bird and ornamentalfish 1 person and 1 farmer.The results of this study indicate that the contract price is stillflexible and more in line with the culture in Demak district, so the risk ofbreeders and collectors can be minimized, but profit can not be enjoyedtogether on both sides (breeders and collectors). The advantage is moreenjoyed by the collecting party as the contract price determinant. Bothparties still have ties to try to foster cooperation to be longer with betterfuture cooperation commitments. Cooperation ties need to be improved soas to become stronger and more profitable. Information generally knownto farmers will be anticipated by the collectors. The agency theory stillapplies to the business of cricket trade. The collectors still hide veryimportant information and can threaten the existence of the collectorsthemselves.